Small molecule inhibitors of osteoarthritis: Current development and future perspective - Liu, Dan; Li, Xingxing; Zhang, Lin; Hu, Bin; Hu, Sang; Zhang, Xiao; Hu, Jing (Frontiers in Physiology, 2023)
Osteoarthritis (OA) is one of the common degenerative joint diseases in clinic. It mainly damages articular cartilage, causing pain, swelling and stiffness around joints, and is the main cause of disability of the elderly. Due to the unclear pathogenesis of osteoarthritis and the poor self-healing ability of articular cartilage, the treatment options for this disease are limited. At present, NSAIDs, Glucocorticoid and Duloxetine are the most commonly used treatment choice for osteoarthritis. Although it is somewhat effective, the adverse reactions are frequent and serious. The development of safer and more effective anti-osteoarthritis drugs is essential and urgent. This review summarizes recent advances in the pharmacological treatment of OA, focusing on small molecule inhibitors targeting cartilage remodeling in osteoarthritis as well as the research idea of reducing adverse effects by optimizing the dosage form of traditional drugs for the treatment of osteoarthritis. It should provide a reference for exploration of new potential treatment options.